Changes in fatty acid composition, cholesterol and fat-soluble vitamins during development of eggs and larvae in shabbout (Barbus grypus, Heckel 1843) - Harlioglu, A. G.; Golbasi, S. (Wiley, 2013)
Changes in fatty acid composition, cholesterol and fat-soluble vitamins were studied during development (fertilized eggs, yolk-sac larvae, and after yolk resorption of shabbout, Barbus grypus). Significant differences were found in the monounsaturated fatty acids (MUFAs), polyunsaturated fatty acids (PUFA), PUFA/saturated fatty acids (SFA), Sigma n-3 and eicosapentaenoic acid (EPA)/docosahexaenoic acid (DHA) ratios between eggs and larvae (P<0.05). Significant differences were also observed in the C14:0, C16:1n-7, C18:1n-9, C18:3n-6, C20:0, C20:4n-6, C24:0, C24:1, C22:6n-3 fatty acids between eggs and larvae after yolk-sac resorption (P<0.05). Vitamin - Tocopherol and retinol content increased during embryogenesis, but changes were insignificant in retinol acetate, -Tocopherol, K1, K2 and cholesterol content between eggs and larvae after yolk resorption (P>0.05).
Keywords: Biochemical-Composition; Docosahexaenoic Acid; Senegal Sole; Quality; Lipids